Preparation and characterization of 4-arm star-shaped polylactide-co-poly(ethylene glycol) - Quyen, Tran Ngoc; Khoa, Nguyen Cuu (Vietnam Journal of Chemistry, 2014)
Four-arm star-shaped polylactide-co-poly(ethylene glycol) (4-arm PLA-PEG) was successfully synthesized via two steps. Firstly, ring-opening polymerization (ROP) of lactide with multifunctional initiator, pentaerythritol and stannous octoate (SnOct2) catalyst was conducted at 120 °C. Secondly, star-shaped polylactide was conjugated to monomethoxy-poly(ethylene glycol)-succinic acid (MPEGa) via carbodiimide coupling agent. 1H NMR spectroscopy results indicated that ROP method produced star-shaped polylactide containing a secondary hydroxyl end group in each arm. The molecular weights (GPC) of the resulting macromonomer linearly increased with the increase of the molar ratios of the lactide and pentaerythrytol in feed. The star-shaped macromonomer with hydroxy end groups was used as a macromonomer for block-coupling reaction with MPEGa. The molecular weight distributions of the macromonomers and block copolymers were rather narrow (Mw/Mn:1.1-1.2). The 4-arm polymers PLA-PEG could form gel network via physical bond when the concentration of polymers around 30 %. The gel network can act as a biomaterial for tissue regeneration application. Keywords: Star-shaped, polylactide-co-poly(ethylene glycol), ring-opening polymerization.